A consciência fonológica na alfabetização e a preparação do professor: estudo de caso - Oliveira, Lucimar Ferreira da Silva (2009)
The general objective of this research consists of evaluating the influence of a mini course of teacher formation about the importance of working the phonological conscience in the initial learning of reading, with basis in the principles of the Brazilian Portuguese alphabetic system (SCLIAR-CABRAL, 2003a; b), to prospective teachers whose proposal of work deals with alphabetization with and to literacy. Possible ontological contradictions found commonly in didactic materials adopted in the initial learning of reading are also highlighted, such as: (i) the concept of alphabetization and literacy, even after the introduction of the nine-year Elementary school; (ii) the relation between grapheme and phoneme. Methodologically, such mini course was designed as an integrant part of the proposed contents in a curricular discipline of the 5th semester of Pedagogy, and it was divided into three parts: (i) pre-test: application of ten questions to 14 subjects; (ii) teacher intervention in the application of the mini course; and (iii) post-test: reapplication of the same instrument of evaluation (questionnaire) at the end of the mini course. The methodological/theoretical indications that lead the research is based on the psycholinguistic, advances in neuroscience discoveries about the learning of the initial reading, and the principles of the Brazilian Portuguese alphabetic system (SCLIAR-CABRAL,2003a, p.50-51), regarding the importance of working the phonological conscience in the learning of initial reading. The results show, although the subjects in question had demonstrated lack of methodological/theoretical knowledge about the importance of phonological conscience in the alphabetization, such initial behavior could be eased by the mini course, what points out the importance of discussing more about such subject in class. Some issues have to be discussed: (i) the involving factors in the initial learning of reading, whose focus be the premise that “READING” is different from “LEARNING HOW TO READ” ; (ii) the importance of guaranteeing , in the prospective semesters, linguistics and metalinguistics knowledge, in terms of phonology and the relation between it an the learning of initial reading in the formation of prospective alphabetizer teachers